Design and Implementation of a Web-Based SCADA for Closed-Loop PID Control Optimized by AI with PLC Integration: A Multi-Layer Architecture Integrating Real-Time Monitoring, Intelligent PID Tuning, and Industrial Automation - Ramadhan, Laode Abdikarso Panca; Irawan, Denny (Jurnal Edukasi Elektro, 2025)
This journal aims to design and implement a Web Based SCADA system integrated with PLC and using the Firefly algorithm for PID control parameter optimization in a closed loop system. The system is developed following the ISA-95 architecture on 1st Layer to 3rd Layer, including data collection via PLC, monitoring via SCADA, and AI-based control and analysis. The Firefly algorithm is used to automatically refine the Kp, Ki, and Kd parameters so that the control system works optimally. Testing was carried out on a liquid level control system using the LCV-01 valve control. The results showed that the Firefly method produced faster steady state time and lower overshoot compared to the manual and Ziegler-Nichols methods. The developed Web Based SCADA interface supports real time monitoring, multiuser, historical data trending, and is flexible to access via a browser without special installation. This SCADA-AI-PLC integration provides an adaptive, efficient, and economical solution for modern industrial automation.